2019
DOI: 10.1093/jofore/fvz024
|View full text |Cite
|
Sign up to set email alerts
|

Web Content Analysis of University Forestry and Related Natural Resources Landing Webpages in the United States in Relation to Student and Faculty Diversity

Abstract: Under-representation of minorities and women in natural resources (NR)-related fields is common, both as students and as professionals. The perception of a predominantly white, male student body and workforce is a potential barrier to recruiting women and minorities to Forestry and related-NR fields. The images of “forestry” and “natural resources-related” fields were examined as they would be from a potential student’s perspective looking at university and college websites with these degree program majors at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Changing the forest sector image should be supported with better marketing and promotion on various platforms, both online and offline. One way to promote gender diversity is to highlight diversity in forest sector organization websites, pamphlets, and other media [7]. In higher education, emphasizing diversity on university websites is a central strategy for attracting new student populations.…”
Section: Promoting the Sectormentioning
confidence: 99%
See 2 more Smart Citations
“…Changing the forest sector image should be supported with better marketing and promotion on various platforms, both online and offline. One way to promote gender diversity is to highlight diversity in forest sector organization websites, pamphlets, and other media [7]. In higher education, emphasizing diversity on university websites is a central strategy for attracting new student populations.…”
Section: Promoting the Sectormentioning
confidence: 99%
“…The perception of the forest sector as a male dominated field is not only related to workplaces, but also forestry education. A web content analysis found that images on US forestry universities' websites rarely portrayed women, possibly perpetuating the suggestion of a less perceived fit for women in the forest sector [7]. Perceived fit is a direct measure of fit, the degree to which individuals can see themselves fitting into an organization [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low number of minority students matriculating into natural resource and environmental programs (Blockstein, Mandula, and Ploetz 1992;Lawrence, Holland, and Morrin 1993;Sharik and Frisk 2011) implies that there is little interest to pursue these disciplines among underrepresented groups or there is little perceived fit (Bal and Sharik 2019). How career interests develop and career choices are made is a complex process that has been studied extensively by experts in the field of career development (Krumboltz, Mitchell, and Jones 1976;Vondracek, Lerner, and Schulenberg 1986).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recruitment efforts from agencies and organizations would benefit from including parents when discussing career options to youth. Addressing the broad range of career options and opportunities for upward mobility in many NR careers may help mitigate perceived wage ceilings.While other fields are experiencing a rise in the number of minorities, particularly some traditional STEM fields, lack of diversity continues to be a barrier that deters minorities from the NR field(Bal and Sharik 2019; McGrown 2015). Lack of diversity can lead to feelings of isolation and unrelatability to the majority population.…”
mentioning
confidence: 99%